Self-efficacy is associated with less burden and more gains from behavioral problems of Alzheimer's disease in Hong Kong Chinese caregivers - Cheng, Sheung-Tak; Lam, Linda C W; Kwok, Timothy; Ng, Natalie S S; Fung, Ada W T (The Gerontologist, 2013)
To test the effects of different self-efficacy beliefs on caregiver appraisals and depressive symptoms. We hypothesized that self-efficacy has a direct effect on depression while moderating the effects of behavioral problems on both negative (i.e., burden) and positive (i.e., uplifting) appraisals. Ninety-nine Chinese caregivers of relatives with Alzheimer's disease responded to measures of self-efficacy, positive gains, burden, depression, and care recipient behavioral problems. Data were analyzed using confirmatory factor analysis and multiple regression. Confirmatory factor analysis supported a 3-factor structure for the Revised Scale for Caregiving Self-Efficacy (obtaining respite, responding to disruptive behaviors, and controlling upsetting thoughts). Interaction effects in regression showed that caregivers with higher self-efficacy in controlling upsetting thoughts had more positive gains and less burden when confronted with more behavioral problems. Self-efficacy in obtaining respite had direct effects on burden and depression, and self-efficacy in responding to disruptive behaviors had a direct effect on positive gains, but not moderating effects. The results supported the multidimensional structure of caregiver self-efficacy and showed that efficacy in controlling upsetting thoughts was most important in buffering the effects of behavioral problems on burden and positive gains among Chinese caregivers. Interventions for dementia caregivers may be more effective if more emphasis is given on changing negative thoughts.